Implementing Emotional Intelligence to Prevent and Manage Bullying in School-Aged Adolescents - Aldo Alberto Panjaitan; Kurniawan Dwi Madyo Utomo; Venansius Gapi Ladja; Jekki Tua Sipayung (Universitas PGRI Yogyakarta, 2026)
The rampant bullying in schools has become a serious problem that needs to be addressed immediately. This situation prompts the author to offer an effective solution grounded in emotional intelligence theory. This research aims to offer a solution to tackle the widespread bullying in schools. The research method used is a PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses). Based on the method, 4 scientific journals were found that met the inclusion criteria and were relevant to this research. This study provides implications for schools to take a more serious approach in addressing the widespread phenomenon of bullying, thereby reducing its prevalence in school settings. The findings of this study are the application of the five main areas of emotional intelligence to address bullying in schools. These applications are divided into five parts according to the five main areas of emotional intelligence (self-awareness, self-regulation, self-motivation, empathy, and social skills). Keywords: bullying, teenagers, school, emotional intelligence, Daniel Goleman